Cytotoxicity and Anticancer Activity of [Cu(tet-am)](CH3COO)2.4H2O Complex Against Ehrlich Ascites Carcinoma (EAC) Cells (Journal of Bio-Science, 2026)
Cancer is a fatal disease characterized by aberrant cell proliferation, invasion, and spread to many body parts. Many chemotherapeutics, including metal complex cisplatin and carboplatin, have been utilized in cancer treatment throughout history. However, a lack of selectivity for cancer cells and related adverse effects with present treatment choices have fueled global attempts to find new anticancer drugs. In this study, a metallo-azamacrocyclic complex [Cu(tet-am)] (CH3COO)2.4H2O has been synthesized, and its antineoplastic activity against EAC cells was measured in vivo. To identify the potent chemotherapeutic drug with minimal or no side effects, cytotoxicity, tumor cell growth inhibition, haematological and biochemical parameters were assessed. The complex showed significant antitumor efficacy against EAC cells. It inhibited cell growth by 38.1% and 70.78% at doses of 2.0mg/kg and 4.00 mg/kg i.p., respectively, compared to control EAC-bearing mice (p